Les partis politiques en France - Delwit, Pascal (Science politique, 2014)
Like European political parties, French political parties face a number of challenges and are subject to many tensions at the dawn of the twenty-first century, even though their attractiveness has never seemed so low. arrangement around the Rassemblement pour la Republique (RPR) and the Union for French Democracy (UDF) on the right, and the Socialist Party (PS) and the French Communist Party (PCF) on the left, the party system itself has even considerably evolved under the effect of the recomposition of the parliamentary right, the collapse of the Communist Party or the breakthrough of newcomers, such as the National Front or the Greens. After the sequence of presidential and legislative elections of 2012, this book analyzes in depth the state of each of the active parties in the political system. How does each of them position themselves in relation to the transformations of partisan activity? How do parties interpret the mutations they face? How do they deal with the disaffection they experience? What ideological and organizational evolutions do they know? These issues are discussed in this reference book. The authors present an original overall picture, systematically offering a party analysis at work in the French political system; which is completed by a reflection on the major transformations of the electoral geography.